Chelerythrine Chloride Alleviated Lipopolysaccharide-Induced Acute Lung Injury by Inhibiting Glycolytic Pathway Through Targeting Glyceraldehyde-3-Phosphate Dehydrogenase - He, Yuting; Fan, Tianyun; Zhuge, Ruishen; Li, Huiying; Li, Guanjun; Zhou, Lirun; Xu, Liting; Hao, Xiaojiang; Gu, Wei; Wang, Jigang (Molecules (Basel, Switzerland), 2025)
Acute lung injury (ALI) is a fatal respiratory disease caused by excessive inflammation. Chelerythrine chloride (CH), an isoquinoline alkaloid, exhibits diverse biological activities. The research focused on assessing CH’s therapeutic effects against LPS-mediated ALI in mice and its underlying mechanisms. The anti-inflammatory effects of CH were evaluated both in LPS-induced RAW264.7 cells and ALI mouse model. An amount of 2.5 μM CH significantly inhibited the secretion of nitric oxide (NO), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and IL-1β in RAW264.7 cells. CH treatment notably mitigated the thickened alveolar septa and reduced edema in LPS-induced ALI in mice. Activity-based protein profiling (ABPP) technology was employed to identify the targets of CH. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was one of the direct targets of CH identified by ABPP. CH could downregulate the production of pyruvate. Furthermore, CH reduced the extracellular acidification rate (ECAR) while increasing the oxygen consumption rate (OCR) in LPS-stimulated RAW264.7 cells. All results suggest that CH mitigates LPS-induced ALI by targeting GAPDH and inhibiting glycolysis. This study reveals preliminary anti-inflammatory mechanisms of CH and its therapeutic potential for ALI.